Analysis of the Influence of Digital Banks on Bank Profitability - Lazuardi*, Johan; Muktiyanto, Ali; Budiyanti, Hety (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This article aims to present an analysis of the influence of digital banks on bank profitability in Indonesia in 2013–2021. The research method used is a comparative causal method with secondary data from annual reports of sample banks taken purposively from banks in Indonesia that have provided digital bank transaction services and have gone public from 2013–2021. The results show that the number of digital bank transactions in the form of mobile banking (MB) has a positive effect on bank profitability by controlling liquidity (LDR). This happens because MB transactions are emergency and simple with smaller transaction limits so that the number of MB transactions is large and in line with increasing operational efficiency and bank profitability, and the number of digital bank transactions in the form of Internet banking does not affect bank profitability even though it has controlled liquidity (LDR). ). This is because IB transactions are complex with a nominal limit per transaction that is larger than MB, so the number of IB transactions is smaller than the number of MB transactions. Keywords: Digital Bank; Mobile Banking; Internet Banking; Liquidity; Profitability Abstrak Artikel ini bertujuan menyajikan analisis pengaruh dari bank digital terhadap profitabilitas bank di Indonesia pada tahun 2013–2021. Metode penelitian yang digunakan adalah metode kausal komparatif dengan data sekunder dari laporan tahunan bank sampel yang diambil secara purposive pada bank di Indonesia yang telah memberikan layanan transaksi bank digital dan telah go public dari tahun 2013–2021. Hasil penelitian menunjukkan jumlah transaksi bank digital berupa mobile-banking (MB) berpengaruh positif terhadap profitabilitas bank dengan mengontrol likuiditas (LDR). Hal ini terjadi karena transaksi MB bersifat darurat dan simpel dengan limit pertransaksi yang lebih kecil sehingga jumlah transaksi MB banyak dan selaras dengan peningkatan efisiensi operasional dan profitabilitas bank, dan jumlah transaksi bank digital berupa internet banking tidak berpengaruh terhadap profitabilitas bank walaupun sudah mengontrol likuiditas (LDR). Hal ini karena transaksi IB bersifat kompleks dengan limit nominal pertransaksi yang lebih besar dari MB, sehingga jumlah transaksi IB lebih kecil dari jumlah transaksi MB. Kata Kunci: Bank Digital; Mobile Banking; Internet Banking; Likuiditas; Profitabilitas